Tathwir Al-wasail Ar-raqmiati li ta'lim Al-mufradat bi Istikhdam Thunkable - Fuji, Fuji Astuti; Risa Firliana; Nur Balqis; Rosmiati (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2025)
This study aims to identify the level of validity of digital media for vocabulary learning using Thunkable, identify the level of practicality of using media in vocabulary learning, and identify students' responses to the use of media in vocabulary teaching. The method used in this research is the Research and Development method with the ADDIE model and has five stages namely Analysis, Design, Development, Implementation, and Evaluation, and to collect data this research uses observation, interviews, and questionnaires. The results of this study are: the validity value of the material and language expert is 90% and the method expert is 88%, this shows that digital media using Thunkable is valid and can be used in vocabulary learning, then the usage value of the Arabic teacher is 88%, based on this data that this method is practical to be used by teachers in teaching vocabulary, and the student response value is 92.5%, based on this data that the student response to the use of this digital media is good.